A Comparative Study: The Demographic Differences of Game Literacy - Wahyuni, Lussy Dwiutami; Ariyani, Mira; Hutomo, Bijak Aditia (Universitas Indraprasta PGRI, 2021)
Nowadays, the development of literacy has found the new ways called Game Literacy. It is an approach based on literacy on game design or the ability to understand certain type of meaning. The aim of this study is to find an empirical data about game literacy across demographic factors (age, gender, playing game duration, and game’s genre). The samples of this research are 418 gamers from 23 provinces in Indonesia that taken by nonprobability sampling. Data collected by using google form to the gamer communities and social media groups. The method of this study is comparative study that aims to find the differences between each demographic factors. The result found that there are differences of game literacy referred to age (p=.000), gender (p=.004), and playing game duration (p=.004). Meanwhile, the other result has found that there are no differences referred on game genre (p=.063). The limitation of this research is the developmental stage of the subject. The subject of this study was only taken from early adults and older.